2012
DOI: 10.1080/17518253.2012.718803
|View full text |Cite
|
Sign up to set email alerts
|

A green synthesis of glycoluril derivatives in aqueous solution with recycle of the waste

Abstract: A series of glycoluril derivatives have been synthesized in water at room temperature from urea and 1,2-dicarbonyl compounds in the presence of phosphoric anhydride. The reaction time is about 10 minutes using one mole of 1,2-dicarbonyl compound, three moles of urea, and half mole of P 4 O 10 , but the reaction occurs also, even if with longer reaction times, with very small amounts of P 4 O 10 which is recovered at the end of reactions. In fact, several catalytic turnovers can be performed using the same reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…27 The conventional approach to cyclic ureas involves carbonylation of variously substituted diamines with phosgene. 28,29 Much effort has been made to replace phosgene by its less toxic analogues, such as dialkyl carbonates, 30,31 triphosgene, [32][33][34] 1,1′-carbonyldiimidazole, 35,36 urea, 37 and others. Novel approaches to these compounds, such as the direct carbonylation with carbon monoxide 38,39 or [3+2] cycloaddition of isocyanoacetates with nitrones, 40 are still emerging, indicating a growing area of interest.…”
Section: Published As Part Of the Special Topic Recent Advances In Ammentioning
confidence: 99%
“…27 The conventional approach to cyclic ureas involves carbonylation of variously substituted diamines with phosgene. 28,29 Much effort has been made to replace phosgene by its less toxic analogues, such as dialkyl carbonates, 30,31 triphosgene, [32][33][34] 1,1′-carbonyldiimidazole, 35,36 urea, 37 and others. Novel approaches to these compounds, such as the direct carbonylation with carbon monoxide 38,39 or [3+2] cycloaddition of isocyanoacetates with nitrones, 40 are still emerging, indicating a growing area of interest.…”
Section: Published As Part Of the Special Topic Recent Advances In Ammentioning
confidence: 99%
“…An efficient approach to the green synthesis of glycoluryls in an aqueous medium using P 4 O 10 as a catalyst, under mild conditions with the possibility of recycling both solvent and catalyst, is reported in Ref. [39] More recently, in a number of works [40][41][42] it was found that etidronic acid (HEDP) proved to be a convenient "green" catalyst in 3-component reactions of the formation of dihydropyrimidones using carbonyl compounds with an active methylene group, urea and aldehydes as under traditional conditions, [40,41] and under microwave synthesis. [42] However, examples of the use of HEDP as a catalyst in the reactions of 1, 2-dicarbonyl compounds with ureas are still not known.…”
Section: Introductionmentioning
confidence: 99%
“…An efficient approach to the green synthesis of glycoluryls in an aqueous medium using P 4 O 10 as a catalyst, under mild conditions with the possibility of recycling both solvent and catalyst, is reported in Ref. [39]…”
Section: Introductionmentioning
confidence: 99%
“…The literature [6,7] describes a method for preparing 2,6-dimethyl-4,8-di-tert-butylglycoluril via cyclocondensation of 1-methyl-3-tert-butylurea with glyoxal, in which case a racemic mixture is formed that consists of the three compounds: cis-and trans-isomers of dimethyl-di-tertbutylglycoluril and hydantoin. With that, the yield of trans-isomers was found to be threefold that of cis-isomers [8].…”
mentioning
confidence: 99%